The original description and date of publication of Cylindrophis lineatus and remarks on its type locality (Reptilia: Squamata: Cylindrophiidae) - Figueroa, Alex; Low, Martyn E.y. (Zootaxa, 2021)
The snake genus Cylindrophis Wagler, 1828 belongs to the  monogeneric family Cylindrophiidae comprising 15 species distributed predominately throughout SE Asia, with one extralimital species occurring in Sri Lanka (Bernstein et al. 2020: 535). Cylindrophis lineatus is a rare species known from only eight museum specimens (discussed herein), and a photograph of one live individual from Kuching, Sarawak, East Malaysia (Stuebing et al. 2014: 63). Despite being originally described with Singapore as the type-locality (Blanford 1881: 217, 218), it is currently understood that C. lineatus is endemic to western Sarawak, East Malaysia (Stuebing et al. 2014: 63). Wallach et al. (2014: 204) stated that C. lineatus is also found in Kalimantan, but did not provide any references. This appears to have been followed by Bernstein et al. (2020: 537), who provide a map indicating C. lineatus occurrences in Kalimantan. The original description of Cylindrophis lineatus is conventionally cited as Blanford (1881: 217, 218, pl. 20). Herein, we demonstrate that the authorship and date of publication of this taxon should correctly be Cylindrophis lineatus Dennys, 1880b, and discuss that the type locality should be changed to “Borneo”.